Mass Spectrometric Characterization of HSV-1 L-Particles From Human Dendritic Cells and BHK21 Cells and Analysis of Their Functional Role - Birzer, Alexandra; Kraner, Max Edmund; Heilingloh, Christiane Silke; Mühl-Zürbes, Petra; Hofmann, Jörg; Steinkasserer, Alexander; Popella, Linda (Frontiers in Microbiology, 2020)
Herpes simplex virus type 1 (HSV-1) is a very common human pathogenic virus among the world’s population. The lytic replication cycle of HSV-1 is, amongst others, characterized by a tripartite viral gene expression cascade, the assembly of nucleocapsids involving their subsequent nuclear egress, tegumentation, re-envelopment and the final release of progeny viral particles. During productive infection of a multitude of different cell types, HSV-1 generates not only infectious heavy (H-) particles, but also non-infectious light (L-) particles, lacking the capsid. In monocyte-derived mature dendritic cells (mDCs), HSV-1 causes a non-productive infection with the predominant release of L-particles. Until now, the generation and function of L-particles is not well understood, however, they are described as factors transferring viral components to the cellular microenvironment. To obtain deeper insights into the L-particle composition, we performed a mass-spectrometry-based analysis of L-particles derived from HSV-1-infected mDCs or BHK21 cells and H-particles from the latter one. In total, we detected 63 viral proteins in both H- and L-particle preparations derived from HSV-1-infected BHK21 cells. In L-particles from HSV-1-infected mDCs we identified 41 viral proteins which are differentially distributed compared to L-particles from BHK21 cells. In this study, we present data suggesting that L-particles modify mDCs and suppress their T cell stimulatory capacity. Due to the plethora of specific viral proteins incorporated into and transmitted by L-particles, it is tempting to speculate that L-particles manipulate non-infected bystander cells for the benefit of the virus.